2020
DOI: 10.1080/13674676.2020.1780575
|View full text |Cite
|
Sign up to set email alerts
|

Testing the factor structure of the Francis Psychological Type Scales (FPTS): a replication among Church of England clergy and laity

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…The items in the four original dimensions of the FPTS generally loaded as expected on the correct dimension, confirming previous analyses (Francis et al, 2017;Village, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The items in the four original dimensions of the FPTS generally loaded as expected on the correct dimension, confirming previous analyses (Francis et al, 2017;Village, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…This extends work of the factorial structure of the Francis Psychological Type Scales (FPTS) to include an additional factor related to emotional temperament. The structure of the four components of the FPTS were similar to those identified in previous studies (Francis et al, 2017;Village, 2021). This study has shown that the inclusion of an emotional temperament scale within the framework of the original FPTS seems to work well and allows the assessment of a construct that is related to neuroticism within the revised Eysenck model.…”
Section: Discussionsupporting
confidence: 78%
“…Psychological factors: Two psychological factors were included, psychological type and emotionality. Psychological type preferences were assessed using the FPTS (Francis, 2005;Village, 2021). This is a 40-item instrument comprised four sets of ten forced-choice items related to each of the four components of psychological type: orientation (extraversion or introversion), perceiving process (sensing or intuition), judging process (thinking or feeling), and attitude toward the outer world (judging or perceiving).…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Psychological factors: Two psychological factors were included, psychological type and emotionality. Psychological type preferences were assessed using the Francis Psychological Type Scales (FPTS; Francis, 2005; Francis, Laycock, & Brewster, 2017; Village, 2021). This is a 40-item instrument comprising four sets of ten forced-choice items related to each of the four components of psychological type: orientation (extraversion or introversion), perceiving process (sensing or intuition), judging process (thinking or feeling), and attitude toward the outer world (judging or perceiving).…”
Section: Predictor Variablesmentioning
confidence: 99%
“…The survey was constructed to address a range of discrete but interrelated issues arising from the pandemic, from the national lockdown, and from the Church's response with the national lock-up of churches. Initial analyses of these data examined the experiences of rural Church of England clergy and laity during the pandemic (Village & Francis, 2020), tested the impact of the pandemic on the fragile churches thesis through the eyes of clergy and laity (Francis, Village, & Lawson, 2020, 2021, gave close attention to the experiences of retired clergy , gave close attention to the experience of churchgoers aged seventy and over , explore the effect of psychological type on shaping responses to the pandemic (Francis & Village, 2021c), compared the experience of male and female churchgoers (Francis & Village, 2021d)…”
Section: Introductionmentioning
confidence: 99%